HUBUNGAN GAMBARAN CT-SCAN PARU DENGAN KADAR LIMFOSIT DAN NEUTROFIL PADA PASIEN SARS-COV-2 PADA PERIODE JUNI, JULI, DAN AGUSTUS TAHUN 2021 DI RUMAH SAKIT UMUM VINA ESTETICA MEDAN - Tampubolon, Benny; Anto, Endy Juli; Girsang, Elizabeth (Universitas Methodist Indonesia, 2022)
Background : Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a new type of Coronavirus that is transmitted to humans that attacks the respiratory system and manifests as inflammation of the lung parenchyma. CT-Scan can be used as an alternative diagnostic measure to find out the radiological picture of COVID-19 patients. Neutrophils are present in many acute respiratory distress syndrome (ARDS)-associated lung diseases, as influenza virus and SARS-CoV-1 infection. Neutrophil activation and degranulation occur in SARS infection. The immune response that occurs in COVID-19 patients with severe clinical trials can be found in lower lymphocyte counts. Decreases in helper T cells, suppressor T cells, and regulatory T cells are found in patients with COVID-19, with higher levels of T helper and regulatory T cells. low in severe cases. Research Objectives: To find out whether there is a relationship between CT-Scan Lung images and Lymphocyte and Neutrophil Levels in SARS-CoV-2 Patients, Research Methods: The type of research carried out is observational analytic measurement, with a cross sectional design the researcher makes observations or measurements of variables at certain times. Results: The frequency distribution on CT-Scan images of the lungs of SARS-CoV-2 patients was found to be the most GGO accompanied by infiltrates with a frequency of 22 people (38.6%) and the frequency distribution of Lymphocyte and Neutrophil levels in SARS-CoV-2 patients. The highest number of lymphocytes in patients with SARS-CoV-2 was normal with a frequency of 27 people (47.4%) and Neutrophil levels increased with a frequency of 24 people (42.1%). In the analysis there was a significant relationship between CT-Scan images of the lungs and lymphocyte levels, p-values = 0.013 and in Neutrophils with CT-Scan images of lungs of SARS-CoV-2 patients, there was no significant relationship with p-values = 0.092 Conclusion:There is a relationship between the CT-Scan images of the lungs of SARS-CoV-2 patients and the levels of lymphocytes and there is no relationship between the CT-Scan images of the lungs of SARS-CoV-2 patients and the levels of neutrophils in the body.